Global prevalence of hospital admissions for low back pain: a systematic review with meta-analysis. Issue 4 (21st April 2023) - Melman, Alla; Lord, Harrison J; Coombs, Danielle; Zadro, Joshua; Maher, Christopher G; Machado, Gustavo C
Abstract : Objectives: To determine the proportion of low back pain presentations that are admitted to hospital from the emergency department (ED), the proportion of hospital admissions due to a primary diagnosis of low back pain and the mean hospital length of stay (LOS), globally. Methods: We searched MEDLINE, CINAHL, EMBASE, Web of Science, PsycINFO and LILACS from inception to July 2022. Secondary data were retrieved from publicly available government agency publications and international databases. Studies investigating admitted patients aged >18 years with a primary diagnosis of musculoskeletal low back pain and/or lumbosacral radicular pain were included. Results: There was high heterogeneity in admission rates for low back pain from the ED, with a median of 9.6% (IQR 3.3–25.2; 9 countries). The median percentage of all hospital admissions that were due to low back pain was 0.9% (IQR 0.6–1.5; 30 countries). The median hospital LOS across 39 countries was 6.2 days for 'dorsalgia' (IQR 4.4–8.6) and 5.4 days for 'intervertebral disc disorders' (IQR 4.1–8.4). Low back pain admissions per 100 000 population had a median of 159.1 (IQR 82.6–313.8). The overall quality of the evidence was moderate. Conclusion: This is the first systematic review with meta-analysis summarising the global prevalence of hospital admissions and hospital LOS for low back pain. There was relatively sparse data from rural and regional regions and low-income countries, as well as high heterogeneity in the results.